2022
DOI: 10.3390/w14152361
|View full text |Cite
|
Sign up to set email alerts
|

Developing Indicators of Nutrient Pollution in Streams Using 16S rRNA Gene Metabarcoding of Periphyton-Associated Bacteria

Abstract: Indicators based on nutrient-biota relationships in streams can inform water quality restoration and protection programs. Bacterial assemblages could be particularly useful indicators of nutrient effects because they are species-rich, important contributors to ecosystem processes in streams, and responsive to rapidly changing conditions. Here, we sampled 25 streams weekly (12–14 times each) and used 16S rRNA gene metabarcoding of periphyton-associated bacteria to quantify the effects of total phosphorus (TP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
1
1
Order By: Relevance
“…Genetic approaches like 16S rRNA amplicon sequencing have been used in other systems to better understand planktonic bacterial responses to increasing nutrient concentrations. In other less modified watersheds prone to P enrichment, bacteria begin to respond to increasing TP at 0.052 mg L −1 (upper limit of response range = 0.195 mg L −1 ) (LeBrun et al, 2018a;Pilgrim et al, 2022), which is a considerably lower than our observation of 0.080 mg L −1 (upper limit of response range = 0.220 mg L −1 ). Bacterial responses along TN gradients also occurred at lower, ranges from 0.275-0.9 mg L −1 (LeBrun et al, 2018a;Wagenhoff et al, 2017) in other watersheds compared to our observed range of 0.420-1.020 mg L −1 .…”
Section: Secondary Drivers Of Bacterial Diversitycontrasting
confidence: 77%
See 1 more Smart Citation
“…Genetic approaches like 16S rRNA amplicon sequencing have been used in other systems to better understand planktonic bacterial responses to increasing nutrient concentrations. In other less modified watersheds prone to P enrichment, bacteria begin to respond to increasing TP at 0.052 mg L −1 (upper limit of response range = 0.195 mg L −1 ) (LeBrun et al, 2018a;Pilgrim et al, 2022), which is a considerably lower than our observation of 0.080 mg L −1 (upper limit of response range = 0.220 mg L −1 ). Bacterial responses along TN gradients also occurred at lower, ranges from 0.275-0.9 mg L −1 (LeBrun et al, 2018a;Wagenhoff et al, 2017) in other watersheds compared to our observed range of 0.420-1.020 mg L −1 .…”
Section: Secondary Drivers Of Bacterial Diversitycontrasting
confidence: 77%
“…Lastly, we ranked variables based on response strength (maximum summed z ‐score) to identify which variables were most likely to induce community‐level responses. TITAN has been used recently in other systems to identify bacterial responses to stressor gradients using amplicon sequencing data (Pilgrim et al, 2022; Simonin et al, 2019). Because median D p generally decreased with increasing agricultural land use while sediment nutrients and dissolved ions increased, the negative response for median D p is shown next to the positive responses for other variables to better represent the impacts of increasing agriculture.…”
Section: Methodsmentioning
confidence: 99%
“…Caulobacterales were reported to be more common in low total N and P environments [42]. Caulobacterales and Sphingomonadales populations are promoted in higher temperatures, lower concentrations of oxygen, and increased dissolved organic matter [43].…”
Section: Discussionmentioning
confidence: 99%
“…To date, relatively few studies have attempted to monitor microbial DNA as a routine tool to monitor freshwater catchments [ 24 , 27 , 43 ], with assessments of fish and macroinvertebrate communities remaining more common [ 15 ]. Capitalising on decades of research facilitating the establishment of macroinvertebrate indices of community health, early efforts used regression analyses to identify microbial community attributes associated with different macroinvertebrate community compositions (i.e., macroinvertebrate community types indicative or poor- to high-quality stream environments, Lau et al [ 27 ]) .…”
Section: Discussionmentioning
confidence: 99%